PLANNING AND DEVELOPING CREATIVITY THROUGH MEDIA-BASED LEARNING IN ENGLISH LANGUAGE TEACHING - Mustasyfa Thabib Kariadi; M. Riyanton; Dini Anggraheni (English Review: Journal of English Education, 2021)
This paper justifies the planning and development of teachers' creativity through media-based learning in English language teaching, especially in the pandemic era. This study used a descriptive-qualitative method with a case study. The data sources consisted of 37 English teachers, school principals, and students involved in the teaching and learning process in SMP 7 Purwokerto. The results showed that the teacher's creativity at the planning stage was demonstrated by consistently well-arranged planning the lessons and adequately preparing the learning media regarding the implementation of multimedia. Regarding creativity at the preliminary stage, ESL teachers employed various mediums to make it easier for pupils to acquire and grasp the topic. Audio, visual, and audiovisual media are examples of media. Audio and visual media were the most commonly employed in ELT classes. The planning and creativity teachers become the main factors to make the class more interactive using several media.